Animal Models for Neuroinflammation and Potential Treatment Methods - Tamura, Yasuhisa; Yamato, Masanori; Kataoka, Yosky (Frontiers in Neurology, 2022)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a debilitating chronic disease of unknown etiology and without effective treatment options. The onset of ME/CFS is often associated with neuroinflammation following bacterial or viral infection. A positron emission tomography imaging study revealed that the degree of neuroinflammation was correlated with the severity of several symptoms in patients with ME/CFS. In animal studies, lipopolysaccharide - and polyinosinic-polycytidylic acid-induced models are thought to mimic the pathological features of ME/CFS and provoke neuroinflammation, characterized by increased levels of proinflammatory cytokines and activation of microglia. In this review, we described the anti-inflammatory effects of three compounds on neuroinflammatory responses utilizing animal models. The findings of the included studies suggest that anti-inflammatory substances may be used as effective therapies to ameliorate disease symptoms in patients with ME/CFS.